(untitled) (Journal of the College of Basic Education, 2022)
In this work we introduce a new concept of Mc-functions namely M-gc functions, these are the functions f: X⟶Y in which the inverse image of every compact set in Y is g-closed in X. Several theorems about this concept were proved, and the relationships of M-gc functions with other types of functions were discussed